Risk factors associated with injury and concussion in sanctioned amateur and professional mixed martial arts bouts in Calgary, Alberta. Issue 1 (5th July 2018) - Curran-Sills, Gwynn; Abedin, Tasnima
Abstract : Background: There is limited literature that examines risk factors for injury and mild traumatic brain injury (mTBI) in mixed martial arts (MMA). An examination of previously unstudied bout and athlete characteristics that may pose health risks while partaking in this sport is warranted. Hypothesis/purpose: To determine the incidence of injury and concussion, along with the identification of risk factors that contribute to injury and mTBI in amateur and professional MMA bouts in Calgary, Alberta. Study design: A retrospective cohort study with case–control design. Methods: Calgary amateur and professional MMA records were examined from 1 January 2010 to 31 December 2015. Descriptive statistics were used to describe the incidence of injury and concussion, along with univariate and multivariable logistic regression to identify risk factors for injury and mTBI. Results: The injury rate per 100 athlete exposure (AE), the injury rate per 100 min of exposure and the concussion rate per 100 AE were 23.6 (95% CI 20.5 to 27.0), 4.1 (95% CI 3.48 to 4.70) and 14.7 (95% CI 11.8 to 17.2), respectively. The most common location of injury was the head and mTBI was the most common type of injury. Athletes whose bout was finished by a knockout/technical knockout, corner stoppage, draw, no contest or physician, and those whose country of origin was non-Canadian, were more likely to sustain an injury. No risk factors for concussion were shown to be significant. Conclusion: Engaging in MMA exposes athletes to inherent risk and several recommendations are proposed to reduce these risks. Future prospective investigations are necessary to better delineate the findings in this study.